Academic leveling program and academic performance of students - Pumayauri de la Torre, Laddy Dayana (2019)
Objective. To determine correlation between the Academic Leveling Program and academic performance of students of 1st semester of Universidad de Huanuco in subjects such as Basic Mathematics I and Language I, during 2018-I semester. Methods. A quantitative, descriptive, retrospective correlational study was carried out. The population was made up of 2075 students and a non-probability sample of 276 students, distributed in 14 academic programs offered by the University. To collect the data, written tests and student’s grades report obtained during the implementation of the Leveling Program were used. Pearson’s correlation was used for inferential analysis of results. Results. Regarding the correlation between Academic Leveling Program and academic performance of students of the first semester, a Pearson correlation coefficient (r) of 0.36 (p <= 0.000). Conclusion. The Academic Leveling Program, implemented by Universidad de Huanuco during the period 2018-I, improves the academic performance of students of the first semester in subjects such as Basic Mathematics I and Language I.